The complexity of playing in early childhood education: reflections on the ludic-agressive play - Raquel Firmino Magalhães Barbosa; Maria Cecília da Silva Camargo; André da Silva Mello (Journal of Physical Education (Maringá), 2020)
It analyzes the complexity of the child's play in the context of Early Childhood Education, above all, ludic-aggressive play. It adopts the ethnographic research, developed with 40 children, and a Physical Education teacher from a Municipal Center for Early Childhood Education (CMEI) in Vitória/ES, with participant observation of Physical Education classes and playground, in which the narratives, enunciations and playful episodes were systematized in field diary and through videos. The daily (re)inventions of children in the production of ludic-aggressive play, which, in a veiled and cunning way, give meanings to their playful practices. It seeks to deconstruct pejorative representations about this type of playful manifestation, signaling to its importance in the process of socialization of children and the reorientation of pedagogical practices in the Early Childhood Education context.